PERCEPTIONS OF TEACHERS AND ADMINISTRATORS REGARDING THE E-SCHOOL APPLICATIONS - Atici, Buenyamin; Kucukarslan, Nazli Gueltekin (Babes-Bolyai Univ, 2010)
The education area is one of the most important areas of investment made in the management information systems in Turkey. This study aims to determine the opinions of the teachers and school administrators concerning the e-School applications which were applied in Turkey starting with the academic year 2007-2008. The sample of the study is composed of 241 teachers and 22 school administrators who work in 16 schools, which were selected without a sampling method or proportion. The data were collected by means of a survey and a personal information form. T test and paired groups t test were used to analyze the data. According to the findings of the study no meaningful difference is found between the opinions of the teachers and school administrators concerning e-School applications, the provinces in which they work, their duty places, duties and genders. The research found an increase in the level of teachers and school administrators that use computer and internet before and after introducing e-School applications.